In vivo kinematic analysis of failure cases after nonanatomical anterior cruciate ligament reconstruction: a preliminary study - Tomofumi Kage; Shuji Taketomi; Tetsuya Tomita; Takaharu Yamazaki; Ryota Yamagami; Kenichi Kono; Kohei Kawaguchi; Ryo Murakami; Takahiro Arakawa; Takashi Kobayashi; Hiroshi Inui; Sakae Tanaka (Knee Surgery & Related Research)
Abstract Background Nonanatomical anterior cruciate ligament (ACL) reconstruction occasionally induces ACL failure without an evident injury episode, necessitating revision surgery. Although the in vivo kinematics of ACL deficiency before primary ACL reconstruction are well documented, the kinematics of ACL failure after nonanatomical reconstruction remain unexplored. The aim of this study is to investigate ACL failure kinematics following nonanatomical reconstruction. Patients and methods This study enrolled three patients with ACL failure after nonanatomical reconstruction, 20 normal and 16 ACL-deficient knees. The anteroposterior (AP) translation of the medial and lateral femoral condyles and center of the femur and femoral rotation relative to the tibia during squatting were evaluated using a two- to three-dimensional registration technique under fluoroscopy. Results Medial AP translation of the nonanatomically reconstructed knee in one patient showed posterior location and abnormal kinematics compared with the ACL-deficient knees. In contrast, the lateral AP position of the nonanatomically reconstructed knees in two patients were more posteriorly located and showed more abnormal kinematics than the ACL-deficient knees. Central AP translation of the nonanatomically reconstructed knees in two patients was located more posteriorly throughout the range of midflexion. Femoral rotation of the nonanatomically reconstructed knees showed abnormal kinematics compared with that of the normal and ACL-deficient knees. Conclusions By independently assessing the medial and lateral aspects of the femur, the medial or lateral condyle of the femur of nonanatomically reconstructed knees exhibited a more pronounced abnormality compared with ACL-deficient knees. The femur of the nonanatomically reconstructed knees showed abnormal rotational kinematics. Considering the kinematic aspect, nonanatomical ACL reconstruction should be avoided.